Encyclopedia of quality of life and well-being research - Maggino, Filomena (Springer eBook Collection, 2020)
This 2nd edition is the definite source on issues pertaining to the full range of topics in scientific and other scholarly research on the quality of life, including health-related quality of life research or also called patient-reported outcomes research. Altogether 500 new entries appear in this new edition. This single, multidimensional reference work connects the most salient and important contributions to the relevant fields from the behavioral and social sciences as well as health and healthcare. New topics in this 2nd edition are on disabilities, religion/spirituality, sex, sports, politics, government, science, literature, performance and visual arts, environmental quality and sustainable development. The 2nd edition of the Encyclopedia of Quality of Life and Well-being Research is an indispensable reference point for future research and writing topics on quality of life. .